Respostas

A melhor resposta!
  • Usuário do Brainly
2014-07-23T16:10:45-03:00
A)
   ( \frac{3}{4}) ^{2} .(- 2)^{3}  +(- \frac{1}{2} ) ^{1}=

  \frac{9}{16} .(-8)- \frac{1}{2}  =

- \frac{9}{2} - \frac{1}{2} =- \frac{10}{5} =-5

b)
   ( \frac{1}{2}) ^{-2}  +( \frac{1}{3} ) ^{-1} =

4+3=7

c)
   -2( \frac{3}{2}) ^{3}  + 1^{15} -(-2) ^{1} =

-2( \frac{27}{8} )+1-(-2)=

- \frac{27}{4} +1+2=

- \frac{27}{4} +3=

 \frac{-27+12}{4} =- \frac{15}{4}

d)
     [(- \frac{5}{3} ) ^{-1} +( \frac{5}{2}) ^{-1}  ] ^{-1} =

(- \frac{3}{5} + \frac{2}{5} ) ^{-1} =

(- \frac{1}{5} ) ^{-1} =-5

e)

( \frac{1}{3} ) ^{-3} .0,5 ^{-2} =

8. \frac{1}{0,25} = \frac{8}{0,25} =32

f)
   6(  \frac{2}{3} ) ^{2} +4(- \frac{3}{2} ) ^{-2} =

6( \frac{4}{9} )+4( \frac{4}{9} )=

 \frac{24}{9} + \frac{16}{9} = \frac{40}{9}
2 5 2